2014
DOI: 10.1186/1678-9199-20-37
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of rabies antibodies as a strategy for canine active immunization

Abstract: BackgroundRabies, a zoonosis found throughout the globe, is caused by a virus of the Lyssavirus genus. The disease is transmitted to humans through the inoculation of the virus present in the saliva of infected mammals. Since its prognosis is usually fatal for humans, nationwide public campaigns to vaccinate dogs and cats against rabies aim to break the epidemiological link between the virus and its reservoirs in Brazil.FindingsDuring 12 months we evaluated the active immunity of dogs first vaccinated (booster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…In the studies mentioned above, the age or primary vaccination and lack of a shortinterval booster (or a complement of primary vaccination) appear as the major problems leading to vaccination failure. Reinforcing the importance of complementation of primary vaccination, BABBONI et al (2014) demonstrated that 99% of 576 primo vaccinated dogs receiving a booster 30 days later harbored adequate antibody levels when examined a month later.…”
Section: Discussionmentioning
confidence: 84%
“…In the studies mentioned above, the age or primary vaccination and lack of a shortinterval booster (or a complement of primary vaccination) appear as the major problems leading to vaccination failure. Reinforcing the importance of complementation of primary vaccination, BABBONI et al (2014) demonstrated that 99% of 576 primo vaccinated dogs receiving a booster 30 days later harbored adequate antibody levels when examined a month later.…”
Section: Discussionmentioning
confidence: 84%
“…The Pan American Health Organization (PAHO) has achieved the goal of eradicating rabies by the development of a mass canine rabies vaccine in Latin American countries [ 19 21 ]. These successful experiences suggest that the key to rabies prevention and control is the virus control.…”
Section: Discussionmentioning
confidence: 99%
“…The authors believe that reducing the number of clinic visits and associated costs potentially improves patient compliance with the treatment plan. 15,[27][28][29][30] When used appropriately and timely, rabies PEP is almost 100% effective in preventing the disease. 23…”
Section: Discussionmentioning
confidence: 99%